Smart Kids, Smart Future: Human Resource and Financial Management Education for the Younger Generation PERMAI Penang Island, Malaysia - Nurbaya, Sitti; K., M. Yusuf; Kasim, Muhammad Najib; Japar, Rahayu; Ardiansyah, Fery (PT. Riset Press International, 2025)
This article discusses the results of a Community Service (PKM) activity entitled Smart Kids, Smart Future: Human Resource and Financial Management Education for the Young Generation of PERMAI Pulau Pinang, Malaysia. This activity focused on improving the knowledge and skills of the younger generation in the areas of human resource management, financial literacy, planning, the application of sharia financial principles, and creativity in designing business ideas. Interactive and practical learning methods were applied to ensure that participants not only understood the theory but were also able to implement it in a real-world context. The results of the evaluation through pre-tests and post-tests showed a significant improvement in all indicators measured. Participants' understanding of HR management increased sharply, especially in planning and task distribution. Basic financial literacy and Islamic finance principles also experienced substantial strengthening, enabling participants to integrate financial aspects with Islamic values. In addition, creativity in developing simple business ideas proved the participants' ability to combine knowledge with relevant innovation. Overall, this programme successfully achieved its stated objectives, namely equipping the younger generation with managerial and financial competencies that support economic independence and an understanding of Islamic values. This success provides an important foundation for the development of more comprehensive and sustainable follow-up programmes.